RANCANG BANGUN MOTOR INDUKSI SEBAGAI GENERATOR (MISG) PADA PEMBANGKIT LISTRIK TENAGA MIKROHIDRO - Effendy, Machmud (Departemen Teknik Elektro, Universitas Diponegoro, 2009)
Induction Motor As Generator (IMAG) is an induction motor operated as a generator. IMAG widely applied in micro-hydro power plant (MHPP) with a power of less than 10kW. IMAG has many advantages such as: low price, easier maintenance, and widely available in the market. One of weakness IMAG is output voltage is affected by the load. In this research, we use induction motor 1 phase, 1 HP. In order to function as generator, it takes a capacitor 22 uF. IGC (Induction Generator Controller) is used to stabilize output voltage IMAG result of changes in load. IGC uses voltage censor to detect the change of consumer load. Voltage censor proceses linerarity level to the change of output voltage IMAG which equals to R2=0.995. The use of IGC causes the IMAG voltage is approximately 220.9 V to 224.7V and the IMAG frequency is 49.1 Hz to 50.5 Hz. Keywords: IGC, IMAG, microhydro